Melatonin Modulates Lipid Metabolism in Porcine Cumulus–Oocyte Complex via Its Receptors - Zhu, Tianqi; Guan, Shengyu; Lv, Dongying; Zhao, Mengmeng; Yan, Laiqing; Shi, Li; Ji, Pengyun; Zhang, Lu; Liu, Guoshi (Frontiers in Cell and Developmental Biology, 2021)
Lipid is crucial energy resource for mammalian oocyte. Melatonin could benefit the maturation of porcine oocyte in vitro, but the related mechanism is not elucidated yet. In the current study, methods to monitor lipids metabolism in single live oocyte were firstly established using probes (Lipi-Blue and Lipi-Green). It was observed that both lipids biogenesis and lipolysis occurred in maturing oocyte, but the general level of lipids dropped. Then maturing oocytes stained with probes were treated with melatonin or lipids metabolic related inhibitors (Triacsin C, Rotenone or Etomoxir). The results showed that the lipids metabolism and maturation of porcine oocytes were all disrupted and melatonin rescued these oocytes treated with Triacsin c or Rotenone, but not that of Etomoxir. Further investigation demonstrated that cumulus cells are able to transfer lipids to oocytes via gap junctions. It was also observed that melatonin receptors exists in cumulus cells and are required for oocytes to maintain lipids metabolism. Meanwhile, the global gene expressing in cumulus cells was also modulated by melatonin, especially the genes related to antioxidants (SOD1, GPX1, GPX3, GPX4, PRDX2 and PRDX5), lipid metabolism (FABP3, FABP5, ACACB, TECR, etc) and mitochondrial respiration (GPD1, ETFB,CYC1 and the genes of ATP synthase). Altogether, the current research demonstrate that melatonin modulates the lipid metabolism in maturing oocytes through its receptors in cumulus cells and benefits the developmental competence of oocytes.